Prognostic impact of extracellular volume fraction derived from equilibrium contrast-enhanced CT in HCC patients receiving immune checkpoint inhibitors - Xiaona Fu; Yusheng Guo; Kailu Zhang; Zhixuan Cheng; Chanyuan Liu; Yi Ren; Lianwei Miao; Weiwei Liu; Shanshan Jiang; Chen Zhou; Yangbo Su; Lian Yang (Scientific Reports)
Abstract This study aimed to investigate whether extracellular volume (ECV) fraction derived from equilibration contrast-enhanced computed tomography (CECT) affects prognosis in HCC patients receiving ICIs. This retrospective study ultimately included 211 HCC patients undergoing ICIs, of whom 60 were included in an internal validation to assess the reproducibility of the results. Baseline unenhanced and equilibrated CECT were used to measure CT values of the tumor, liver and aorta, which were combined with hematocrit to calculate the ECV fraction. Correlation analysis was used to investigate the association between tumor ECV and liver ECV fractions. The effects of clinical variables and ECV fraction on progression-free survival (PFS) and overall survival (OS) were evaluated using Cox proportional hazards models and Kaplan-Meier curves. Of these 151 patients, tumor ECV fraction positively correlated with liver ECV fraction. In the Lower tumor ECV group, PFS (5.6 vs. 7.6 months) and OS (10.5 vs. 15.5 months) were notably shorter than in the Higher tumor ECV group, while no significant differences were found between the Higher and Lower liver ECV groups. Furthermore, the multivariable Cox regression model demonstrated that higher tumor ECV fraction level was an independent protective factor for PFS and OS (all P < 0.001). Internal validation cohort preliminary demonstrated reproducibility of results. The tumor ECV fraction is expected to become a routine indicator before ICIs therapy for HCC patients in contrast to liver ECV fraction, contributing to their subsequent management.